Recent Advances in Smellscape Research for the Built Environment - Xiao, Jieling; Aletta, Francesco; Radicchi, Antonella; McLean, Kate; Shiner, Larry E.; Verbeek, Caro (Frontiers in Psychology, 2021)
The interrelationships between humans, smells and the built environment have been the focus of increasing numbers of research studies in the past ten years.This paper reviews these trends and identifies the challenges in smellscape research from three aspects: methodological approaches, artistic design interventions and museum practices, and odour policy making. In response to the gaps and challenges identified, three areas of future research have also been identified for this field: smell archives and databases, social justice within odour control and management, and research into advanced building materials.